PENGARUH DIKLAT DAN MOTIVASI TERHADAP KEMAMPUAN GURU MENYUSUN RPP INOVATIF DI GUGUS 06 KECAMATAN BOJONEGORO - administrator administrator; Chusnul Chotimah; Indra Prasetyo; Ruddy Winarko (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
This study aims to describe the ability of teachers in Cluster 06 of Bojonegoro Subdistrict in trainingand motivational teachers. The addition was to find out the training and teacher motivation thatinfluenced the teacher's ability in Cluster 06 of Bojonegoro District. The population in this study wereall teachers of Clusters 06 of Bojonegoro District as many as 35 people. This study uses a quantitativeapproach with an explanatory research type. The number of samples in this study proved to be 35teachers. In this study, researchers used hypothesis testing. Hypothesis testing is done to determine therelationship and influence between variables and dependencies in the hypothesis. The steps taken are bydetermining the influence of the research variables and the price of the hypothesis formulated. The resultsof data analysis showed that the ability of the Cluster 06 District of Bojonegoro teachers in training andmotivational teachers was in good category. What influences the teacher in the education and trainingand teachers in Cluster 06, Bojonegoro District consists of the level of formal education, technicaltraining that has been followed, the ability to master and understand technical tasks.Keywords: education and training, teacher motivation, teacher ability